Integrating the impact of cigarette and waterpipe tobacco use among adolescents in the Eastern Mediterranean Region: a cross-sectional, population-level model of toxicant exposure. Issue 3 (27th June 2016) - Jawad, Mohammed; Roderick, Paul
Abstract : Background: Waterpipe smoking is more prevalent than cigarette smoking among adolescents in the Eastern Mediterranean Region (EMR); however, simple prevalence masks complex waterpipe smoking patterns and makes uncertain its contribution to risk of tobacco-related harm. This study aimed to integrate the impact of cigarette and waterpipe tobacco use on toxicant exposure among EMR adolescents. Methods: A cross-sectional model made equivalent individual-level toxicant exposure data for cigarettes and waterpipes, and aggregated it to 23 countries in the EMR using the Global Youth Tobacco Survey. The waterpipe model adjusted for estimated frequency of use, session duration and sharing behaviours. The final model included 60 306 12–17-year olds, and modelled as outcomes nicotine, carbon monoxide (CO) and 14 carcinogens. Sensitivity analyses substantially reduced session duration and proportion of solo use. Results: Our model suggests waterpipe use may contribute a median of 36.4% (IQR 26.7–46.8%, n=16) of the total toxicant exposure from tobacco, and may reach up to 73.5% and 71.9% of total CO and benzene exposure, respectively. Sensitivity analyses reduced all values by 4.3–21.0%, but even the most conservative scenarios suggested over 50% of benzene and CO exposure was from waterpipe use. Between 69.2% and 73.5% of total toxicant exposure derived from dual cigarette and waterpipe users, who smoked cigarettes and waterpipe more frequently and intensely than single users. Conclusions: More research is warranted to refine our model's parameters. Tobacco control researchers should consider a move towards a single unit of measure for cigarette and waterpipe tobacco exposure in order to better inform health policy.